Barriers and strength factors of adult immunization plans in seven countries of the European region. - Lanza, Teresa Eleonora; Lombardi, Gaia Surya; Tumelero, Serena; Paladini, Andrea; Castagna, Carolina; Cadeddu, Chiara (Journal of Public Health: From Theory to Practice (2198-1833), 2024)
Aim: The present systematic review analyzes existing strategies and policies used for adult vaccination of seven countries of the European area, emphasizing weaknesses and strengths of immunization schedules. Selected countries were Germany, France, the United Kingdom, Italy, Spain, Sweden, and Romania. Subject and methods: Three main scientific databases (PubMed, Scopus, and Web of Science) were queried and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. Studies assessing weaknesses or strengths factors, facilitators and barriers related to the adult vaccination plans were considered eligible. We included ten studies with a medium/high score at the quality assessment. Results: The main barriers and strength factors for vaccination can be divided into the following categories: financial aspects (e.g., if the vaccine has a funding mechanism); logistic factors (e.g., convenience, opening times); factors related to healthcare professionals (e.g., recommendations, provision by different categories of healthcare professionals). Conclusion: Substantial improvement in adult vaccination uptake is urgently necessary to decrease the burden of infectious disease on healthcare systems. Although decision-making regarding adult vaccination is complex and influenced by psychological and personal factors, addressing practical or logistical issues related to immunization plans can facilitate higher vaccination coverage.